The Sensitivity and Specificity of Oral Tumors and Premalignant Lesions Diagnosis by Otolaryngologists - Muhsen, Hussien Jassim (AL-Kindy College Medical Journal, 2008)
Background: Tumors of the oral cavity are under estimated in general dental and medical practice, some authors describe it as the forgetting disease, others wondering if the attention paid to this disease compared to its fatality (The 5-year survival rate is about 50%) is enough for disease control? However; this disease deserves a comprehensive assessment by all dental and medical fields assumed to examine the oral cavity regularly, especially otolaryngologist. Objectives: To find out the sensitivity and specificity of clinical examination in diagnosing oral tumors and premalignant conditions by otolaryngologist. Methods: Across sectional retrospective study was conducted in the: -study design: Cross sectional. -settings: Ear Nose Throat (ENT)departments in Al-kindy Teaching Hospital and Al-Yarmouk Teaching Hospital. On Patients attending ENT department with oral presentation. The outcome variables includes: The sensitivity, specificity, positive predictive value (Pv+ve), negative predictive value (PV-ve), and the accuracy of clinical examination in diagnosing oral tumors and premalignant conditions in ENT clinic. Results: The results revealed a high sensitivity and specificity for otolaryngologist in diagnosing malignant conditions and premalignant lesions of the oral cavity. Conclusion: The study highlights the need for fixed clinical criteria for early diagnosis of premalignant conditions and oral tumors